Comprehensive Approach to Mitigating Solar Photovoltaic Power Penetration Effects in a Microgrid - Youngil Kim; Manef Bourogaoui; Azeddine Houari; Hyeok Kim (International Transactions on Electrical Energy Systems)
High solar photovoltaic (PV) penetration in the electrical grid can result in undesired effects on the voltage quality, leading to line loss and voltage magnitude increases. One of the main criteria to ensure the safe penetration of high-power solar systems in the main grid is maintaining an acceptable voltage magnitude when a disturbance occurs (e.g., 0.95 and 1.05 per unit) with respect to total installed power generation capacity of PV power plants. This manuscript analyzes the effects of high solar PV penetration per unit of voltage stability using the Fast Voltage Stability Index and total power loss. Moreover, we investigate the flexibility benefits of coordinated voltage control based on a smart inverter of solar PV capacitor banks (SI-CBs) under five cases in a typical microgrid (MG) test model. For the test of the SI-CBs, MG modeling is developed on a modified IEEE 123 test feeder, which includes 11 building load solar PVs with smart inverters and capacitor banks with real-time data from an area in Los Angeles, California, USA. The simulation results are presented to validate the effectiveness of the proposed approach using a real-time MATLAB interface to the Open Distribution System Simulator (OpenDSS).